Assessment of the level of awareness of sustainability practices among construction firms in Niger Delta, Nigeria - Otali, Monday; Ujene, Anthony (Penerbit Universiti Kebangsaan Malaysia, 2020)
The importance of sustainable development in Niger Delta, Nigeria cannot be overemphasised. Hence the aim of this research is to assess the level of awareness of sustainability practices among construction firms in Niger- Delta, Nigeria. Data were obtained using 1179 copies of structured questionnaire, administered by the researcher and research assistants. The methods of data analysis were simple percentage, mean score, Kruskal – Wallis and Bonferroni- Dunnett test. The average mean score of 3.48 indicates that the level of awareness of sustainability practices among the construction firms in Niger Delta is high. The P-value is less than 0.05 significance level, hence the hypothesis was rejected. This indicates that there is a significant difference in the level of awareness of sustainability practices among the states in Niger Delta, Nigeria. This study concludes that there is a significant difference in the level of awareness among the states.This study also concludes that level of awareness of sustainability practices among construction firms in Niger Delta is high. It can be inferred that the high level of awareness will lead to high level of adoption of sustainability practices among construction firms which will in turn lead to high performance of the construction firms.